Estudo das curvas de lactação de vacas leiteiras do sudoeste do Paraná: comparação entre modelos empíricos e mecanicistas - Ferreira, Abilio Galvão Trindade (2013)
His work was developed at Federal Technological University of Paraná, Câmpus Dois Vizinhos, aiming to analyze different mathematical models comparing empirical and mechanistic models, as their fit and predictive power of the lactation curves obtained using data from the control of dairy APCBRH herds in the southwest region of Paraná, where the evaluation and analysis of 42.281 controls milk production for the years 2005 to 2011, where information from animals that didn´t have the date of drying and total output to 305 days were excluded from the set of data analysis, leaving 15.142 controls concerning the 2.441 Holstein cows, classifying the data according to the order of calving cows (ranging from one to six) and within each order of calving animals were divided into quartiles (Q25% Q50%, Q75% and Q100%) as the total output to 305 days. For each quartile within each lactation numbers were adjusted four mathematical models, two predominantly empirical model (Brody and Wood) and two with more mechanistic characteristics (model Djikstra and Pollot) using SAS proc nlin Marquardt method. Obtaining the Wood model as a result of best fit to the data. However the use of models and Brody Dijkstra to describe lactation curves of Holstein cows raised in the southwestern region of Paraná, should be considered as an option because they have very similar performance, where the model Dijkistra has a biological description of the parameters and allows a connotation physiological lactation curve. Emphasizing the historical value of the model Brody as a pioneer in modeling lactation curve.